Kinematic analysis of double back straight somersault and double back straight somersault with full twist on rings - Kolimechkov, S.; Yanev, I.; Kiuchukov, I.; Petrov, L. (Science of Gymnastics Journal, 2021)
The rings are one of the six apparatuses in men's artistic gymnastics. The final element in a rings` routine is in many cases a crucial skill for scoring the routine. Most of the medallists on rings from the Olympic Games and World Championships for the last 20 years performed either the double back straight somersault or the double back straight somersault with a full twist. The purpose of this study was to conduct a kinematic analysis of double back straight somersault and double back straight somersault with a full twist on rings. The participants selected for this study were the world-class gymnasts Filip Yanev and Jordan Jovchev. The dismounts were recorded with a DV camera by following a standard method of kinematic analysis. During the execution phase, the ankle speed of Gymnast 1 reached 11.11 m/s and that of Gymnast 2 was 11.29 m/s, and the angular velocity increased substantially to 10.0 rad/s and 9.05 rad/s for Gymnast 1 and 2, respectively. The rotational impulse was sufficient for the successful execution of both dismounts. The actions of Gymnast 2 needed for the full twist, including a small arm asymmetry, began just before releasing the rings. The arching-to-piking action beneath the rings, as well as the powerful pull, combined with a sufficient swing of the legs, are crucial factors for the successful execution of the dismounts.